Preparation of Doughnut-like Nanocomposite Colloidal Crystal Particles with Enhanced Light Diffraction Using Drying Self-assembly Method - Yu, Bing; Cong, Hailin; Yuan, Hua; Liu, Xuesong; Peng, Qiaohong; Zhang, Xiulan; Xu, Xiaodan; Tian, Chao; Yang, Ruixia; Yang, Shujing (Current Nanoscience, 2015)
Doughnut-like nanocomposite colloidal crystal particles with enhanced structural colors were fabricated from monodisperse silica microspheres using droplet templates on polytetrafluoroethylene (PTFE) superhydrophobic surfaces. The structural colors of the doughnut-like particles were greatly enhanced by incorporating carbon black nanoparticles (CB-NPs) into the voids of silica colloidal crystals in the drying self-assembly (DSA) process. The presence of CB-NPs in the structure did not lead to a shift of the reflection band, but enhanced the diffraction color by increased reflectance and suppressed transmission. The lack of physical contact and adhesion to the PTFE superhydrophobic surface allowed the easy detachment of the final assemblies from the substrate, which in turn made possible the large-scale production of the doughnut-like nanocomposite colloidal crystal particles.
Keywords: colloidal crystals